Interactive Module based on Epub to Improve Understanding on Narrative Text for Class IX Junior High School Students - Arianti, Dwi; Degeng, I Nyoman Sudana; Sitompul, Nurmida Chaterine (Jurnal Inovasi Teknologi Pendidikan, 2022)
This study aims to develop an Interactive Module product that is expected to improve the understanding of Narrative Text material in class IX SMP students. Knowing the feasibility of the Sigil-based Interactive Module product to improve understanding of Narrative Text material in class IX SMP students. And knowing the effectiveness of the Interactive Module product to improve the understanding of Narrative Text material in class IX SMP students. This development research refers to the development design steps developed by Alessi & Trollip. The development design is grouped into three development procedures, which include: (a) the planning stage, (b) the design stage, and (c) the development stage. This research (1) produces an interactive English module in the form of a digital ebook that is packaged as an Epub and is equipped with a manual that students can use as a learning resource to support English lessons with Narrative Text material. The resulting development product is considered very feasible to improve students’ understanding of Narrative Text material based on the assessment of English material experts, Learning media experts, and test subjects, and (3) the resulting product is generally considered quite effective in increasing students’ understanding of students’ Narrative Text material class IX SMP N One Roof, as evidenced by the average pretest score of 30.75, an increase in the posttest of 79.25 with a gain score of 0.70.